Promotion of alcohol on social media as a factor hindering the process of addiction treatment - Michał Ziemba; Karolina Ejsmont-Sowała; Dominika Hakało; Marta Ignatiuk-Chilkiewicz; Joanna Kałuska; Katarzyna Nowicka; Wiktor Klimek; Aleksandra Sokół; Klaudia Mościszko; Maria Majewska (Quality in Sport)
Introduction: Alcohol consumption is still high. We can distinguish people who drink heavily, binge drink or people diagnosed with AUD. These people have to fight against unabated temptations during the treatment of their addiction. We decided to check whether exposure to alcohol advertisements in the media actually has a negative impact on the process of treating alcoholism.